Status of incidence of cervical cancer in the Republic of Tajikistan - N. A. Abdugaffarova (Опухоли женской репродуктивной системы)
Background. Cervical cancer (CC) still occupies a leading position in the structure of oncological diseases in the world. In the Republic of Tajikistan, there is a tendency for the growth of oncological diseases, and CC is consistently ranked second.Objective: comparison of overall incidence rates of CC in the Republic of Tajikistan for the period from 2000 to 2020.Materials and methods. To track the dynamics of CC in the structure of cancer incidence, we studied the data of reports on diseases of malignant neoplasms according to forms No. 7 and No. 35 of the Agency on Statistics under the President of the Republic of Tajikistan for the period 2000–2020.Results. The incidence rates of cervical cancer in the republic ranged from 4.7–8.7 per 100,000 of the female population. A similar incidence of cervical cancer is noted in the most densely populated regions – Khatlon (3.5–9.9 per 100,000 female population) and Sughd (5.9–10.8 per 100,000 female population), lower rates in districts of republican subordination (3.3–7.9 per 100,000 women), and in the Gorno-Badakhshan Autonomous Region, the rates varied from 4.6 to 14.7 per 100,000 women, being the highest. CC most often occurred at the age of 35–64 years. CC can be detected at stages I–II in 65–83 % of cases. In 10–19 %, this is a locally advanced process that characterizes the III stage of the disease, and on average, every tenth patient with CC treats with an advanced process (stage IV). Every year, 50–93 % of patients die from the number of newly diagnosed cases. The highest rates of newly diagnosed cases of malignant neoplasms were noted in the B. Gafurov district – from 154 to 198 patients. In Panjakent and Kushoniyon district, these figures are 7–10 times lower: 27–74 and 23–44 cases, respectively. CC was the leading nosology in the structure of oncological morbidity in the Kushoniyon district, while in the district of B. Gafurov and the city of Penjikent, breast cancer was the leader for all the years under study.Conclusion. Regional features can have a direct impact on the system of practical health care and their ability to provide quality care to the population, i. e. the remoteness and inaccessibility of the regions of residence determine the possibility of providing full-fledged medical care to the population, and, as a result, higher mortality rates from malignant neoplasms, in particular, CC. Consequently, our republic needs new approaches and views to reduce the mortality of women from CC in conditions of limited resources.